2016
DOI: 10.5811/westjem.2016.2.29779
|View full text |Cite
|
Sign up to set email alerts
|

Authorship Trends of Emergency Medicine Publications Over the Last Two Decades

Abstract: IntroductionWith the recent merger of the American Osteopathic Association (AOA) and the Accreditation Council for Graduate Medical Education (ACGME) a heightened pressure for publication may become evident. Our objective was to determine whether there was a gap in the type of both medical degree designation and advanced degree designation among authorship in three United States-based academic emergency medicine journals.MethodsWe reviewed the Journal of Emergency Medicine, Academic Emergency Medicine and Anna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…Based upon the data, very few of those DOs who published research manuscripts held a dual degree. Similar data has also been seen by those DOs who have published manuscripts in emergency medicine and obstetrics and gynecology [4-5]. Current literature shows that those pediatric hospitalists who hold a dual degree are more likely to publish original research and present research abstracts at scientific conferences [7].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Based upon the data, very few of those DOs who published research manuscripts held a dual degree. Similar data has also been seen by those DOs who have published manuscripts in emergency medicine and obstetrics and gynecology [4-5]. Current literature shows that those pediatric hospitalists who hold a dual degree are more likely to publish original research and present research abstracts at scientific conferences [7].…”
Section: Discussionsupporting
confidence: 58%
“…Much like in emergency medicine and obstetrics and gynecology, osteopathic physicians rarely published original research manuscripts in the studied three high-impact pediatric journals over the time period studied [4-5]. Data has shown that of the 57,542 active physicians in pediatrics in 2015, 71.06% held an MD degree [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Additionally very few osteopathic physicians have published in the Journal of Emergency Medicine, Academic Emergency Medicine, or Annals of Emergency Medicine over the last two decades despite a trend for increased publication by publication of allopathic physicians; notably, there was not a similar trend for increased publication of osteopathic physicians in emergency medicine. 11 A recent study aimed at determining if a medical degree disparity (between allopathic and osteopathic) existed between those who successfully received an EM R01 grant and those who did not. This study found that allopathic physicians comprised the majority of recipients who were awarded an R01 grant in EM over the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation‐based research is also important to the promotion and professional development of simulation academic faculty. The ACGME, and specifically the EM Residency Review Committee, requires that residency program core faculty “establish and maintain an environment of inquiry and scholarship with an active research component” and demonstrate scholarship via “publication of original research or review articles in peer reviewed journals, or chapters in textbooks.”…”
mentioning
confidence: 99%